The Mahanian Philosophy and its Influance upon Foreign Policy of the United States (1840-1914) - أحمد النصيري عبد الرزاق; ناظم شاكر حيدر (Journal of College of Education, 2020)
There were several factors that had participated in the development of U.S. Navy, and Foreign Policy through History, such as the cultural belief knowing as “Manifest Destiny”, that was widly spread among Americans, during the 19th. Century, which alleged that for the United States Destiny is to continue its territorial expantion westward. Not to mention other factors such as; the International Cometition especially in the Pacific, among other factor, Yet Alfred Mahan’s writings, and philosophy were the most effective factor that revolutionized American Navy ever since. In addition to it’s effect locally, Mahan’s Philosophy were also famous internationally, to thw point that his writings were considered field guide of Sea Wars techniques, and Naval Force machinism, which being tought all around the world until current time. Due to the admiration that Mahan’s writings gained among policy-makers in the United States, his Thiories helped shaping the U.S. Naval Force, and, the political atmosphe, which led eventually to the changing in the Path of Foreign Policy of the U.S., as well as the Future of the Region and the Pacific ever since.